The Use of Audio-Visual Assisted Google Classroom for Mathematics Course - Setiawan, I M Dedy; Ari Oka, I D G (Universitas Pendidikan Ganesha, 2020)
The use of technology in the form of mathematics learning media has not been maximally applied amidst the rapid advances in technology today, coupled with a change in learning patterns from face-to-face in class to online learning patterns due to calls to work from home. This of course will have an impact on the learning outcomes of students. Seeing these conditions, innovation is needed in mathematics learning, namely by utilizing the use of media in learning, one of which is the use of audio-visual media assisted by google classroom. The purpose of this research is to determine the effect of using audio-visual media assisted by google classroom on mathematics courses at STMIK STIKOM Indonesia. The research method used was a quasi-experimental with a non-equivalent control group design. The instrument used in this study was a mathematics learning outcome test. The data analysis technique in this research includes descriptive analysis. The results showed that there was an effect of the use of audio-visual media on mathematics learning outcomes with an average score of 76.00 mathematics learning outcomes which was declared significant so that learning using audio-visual media had an effect on mathematics learning outcomes.